Muenke syndrome. Issue 1 (January 2015) - Addissie, Yonit A.; Yarnell, Colin M.P.; Kruszka, Paul; Muenke, Maximilian
Abstract : Muenke syndrome is an autosomal dominant disorder characterized by coronal suture craniosynostosis, hearing loss, developmental delay, and carpal and tarsal fusions. Reduced penetrance and variable expressivity contribute to the wide spectrum of clinical findings in Muenke syndrome. Muenke syndrome constitutes the most common syndromic form of craniosynostosis, with an incidence of one in 30 000 births and is defined by the presence of the p.Pro250Arg mutation in FGFR3 . Clinical diagnosis is difficult because of phenotypic overlap with other craniosynostosis syndromes, and diagnosis is always made by molecular testing. Optimal management of patients involves a coordinated, multidisciplinary team familiar with the condition.